Rocks and rock formations : a key to identification - Meyer, Jürgen, 1945- (Princeton field guides., 2021)
The first field guide that allows amateur rock enthusiasts to identify basic rocks and rock formations in a systematic wayMany of us are fascinated by rocks--but identifying them can seem daunting. It's often tricky even for geologists, who rely on experience, intuition, and in-depth familiarity with rock-forming components. Rocks and Rock Formations allows everyone, amateur or professional, to successfully distinguish these amazing masses of minerals, using only careful observation, a magnifying glass, a pocket knife--and a bit of patience. J|rg Meyer provides a structured approach to the identification of all rocks within the three groups: sedimentary, igneous, and metamorphic. Bringing together more than 530 diagrams and photographs to illustrate essential characteristics, Meyer highlights some basics on rocks--their mineral constituents, structures, textures, fossils, weathering patterns, and more--which are important for a determination. The main part of the book is a handy and thorough identification key, which takes into account all possible rock variations, mixtures, and structural differences. The concluding section of the guide delves into rock systematics. Assuming little prior experience or knowledge, Rocks and Rock Formations is an invaluable resource for rock enthusiasts everywhere. Suitable for beginners and amateursHelpful, systematic identification keyExploration of all types of rocksMore than 530 diagrams and photographs.